O uso de suplementos proteicos na prática de atividades físicas: uma revisão sistemática - Gomes, João Luís Pereira (Universidade do Vale do Rio dos Sinos, 2014)
The aim of this study is to present a literature review in the area of protein supplementation for practitioners of physical activities, trained or not. Food supplements are requesting, for some time, special attention, since they are embedded in a broad recommendation to use for both, athletes and untrained. The reasons for this increase in the manufacturing and consumption of supplements are multifactorial, as an example, we can mention the pursuit of the perfect body, greatly influenced by the media, and the restriction of supply by avoiding the high energy content, but mainly associated with the impossibility to follow a natural and healthy diet, either for lack of time, unwillingness to buy food or any other factor that brings difficulties in maintaining this diet and regularity. The search was performed in electronic databases and reference lists of identified articles. The following descriptors, in Portuguese and English, were used: "exercise", "strength", "protein supplement", "adults", “whey protein”, “creatine”, “BCAAs”. The initial electronic search yielded 181 articles between proteinuria whey, creatine and branched chain amino acids (BCAA). Of the 38 articles found with BCAA, none of them met the inclusion criteria in this review, so they were all excluded from the review process. The process of analysis of the two studies indicate that supplementation studied (whey protein and creatine) are really effective, in terms of strength, endurance and strength gain, main concern of this study.
Keywords: Suplementos; Proteína; Força; Resistência; Supplements; Protein; Strength; Endurance; ACCNPQ::Ciências da Saúde::Nutrição